Strategi Pembiasaan Akhlak Terpuji Melalui Mata Pelajaran Akidah Akhlak di Madrasah Ibtidaiyah - Syafi'i, Muhammad Imam; Mubarok, Ramdanil; Yuliana, Yuliana (Universitas Islam Ahmad dahlan, 2024)
This research aims to analyze the commendable morals that are taught through moral aqidah lessons, and the habituation strategies for students at Madrasah Ibtidaiyah. The method used in this research is a descriptive qualitative research method. This research was carried out at MI Hajar Abyadl, North Sangatta. There were ten subjects consisting of school principals, teachers and students. The results of the research show that the commendable morals that are taught through moral aqidah subjects are; Shaking hands by kissing older people (polite), praying before and after studying, praying before and after eating (tawakkal), performing the Dluha prayer, performing the midday prayer in congregation, muroja'ah memorize the Al-Qur 'an and Hadith (diligent), cooperation (helping each other), apologizing when you make a mistake (humble), sharing food with friends (generous), doing assignments (responsible), not cheating on exams (honest), and not mocking friends (tolerance). The strategies for habituating commendable morals through the Moral Aqidah subject are: providing an example, giving advice, making habits, and giving punishment. This strategy then collaborates in moral learning, science, leadership, entrepreneurship, and school programs.